The internet of things what everyone needs to know - Shackelford, Scott J. (What everyone needs to know, 2020)
"Many of us go about our daily lives completely-some might say blissfully-unaware that we are surrounded by a cornucopia of devices that are running on various connected platforms and recording our physical presence, voices, heartbeats, and preferences. Have a look around you. Beyond your computer, tablet, or smartphone, how many 'things' that you see are connected to the Internet, either directly or indirectly? Are you wearing a Fitbit or an Apple Watch or using Airpods? Is there an Echo or Google Home in range? What about a connected fridge or smart laundry appliance? How far is the nearest Wi-Fi connected doorbell, light bulb, printer, or diaper? What about your heating and air conditioning and security systems? Now, do you know what data each of these devices is busily recording - or how that data is used or protected? What about the device itself - do you trust it to function consistently and safely? Does it matter? There is a great deal of buzz surrounding the Internet of Things (IoT), which is the notion, simply put, that nearly everything in our physical world - from gym shorts to streetlights to baby monitors, elevators, and even our own bodies - will be connected in our digital world. The Internet of Everything (IoE) (a term that Cisco helped to pioneer) takes this notion a step further by referring to not only the physical infrastructure of smart devices and services but also their impacts on people, businesses, and society.In the end, this book-indeed, dare we say no stand-alone volume-can do justice to the myriad opportunities and risks replete in the Internet of Things. But, our hope is that, by the end, you will feel like we at least did justice to unpacking some of the most important issues and concepts in this new frontier of technology and governance. There are no panaceas or magic bullets, and necessary policy or technological changes will not happen overnight; even the "Blockchain of Things" has its limits, as we will see. Dealing with formidable challenges, such as the pace of technological change or the realization of social and political rights online and offline, takes sustained effort. But, as Rev. Dr. Martin Luther King Jr. said in reference to the U.S. civil rights movement, "If you can't fly, then run. If you can't run, then walk. If you can't walk, then crawl, but by all means, keep moving." In that spirit, let's get started!"